A multiplex platform for digital measurement of circular DNA reaction products - Björkesten, Johan (Nucleic Acids Res, 2020)
Digital PCR provides high sensitivity and unprecedented accuracy in DNA quantification, but current approaches require dedicated instrumentation and have limited opportunities for multiplexing. Here, we present an isothermal platform for digital enumeration of DNA reaction products in multiplex via standard fluorescence microscopy. Circular DNA strands, which may result from a wide range of molecular detection reactions, are captured on streptavidin-coated surfaces via hybridized biotinylated primers, followed by rolling circle amplification (RCA). The addition of 15% polyethylene glycol 4000 during RCA resulted in uniform, easily recorded reaction products. Immobilized DNA circles were visualized as RCA products with 100% efficiency, as determined by droplet digital PCR. We confirmed previous reports about the influence on RCA by sequence composition and size of RCA templates, and we developed an efficient one-step restaining procedure for sequential multiplexing using toehold-triggered DNA strand displacement. Finally, we exemplify applications of this digital readout platform by demonstrating more than three orders of magnitude improved sensitivity by digital measurement of prostate specific antigen (PSA) (detection threshold ∼100 pg/l), compared to a commercial enzyme-linked immunosorbent assay (ELISA) with analogue readout (detection threshold ∼500 ng/l), using the same antibody pair.